The Prediction of Mental Health Based on Social Problem Solving and Self-Efficacy among undergraduate students - Abolmaali, Khadijeh; Barkhordari, Parvaneh (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The purpose of this study was to predict mental health and its components (somatic symptoms, anxiety and insomnia, social dysfunction and depression) based on social problem solving (SPS), and self-efficacy. SPS have 2 problem solving orientations: negative and positive orientation to problem solving (NPO and PPO), and 3 problem solving styles: rational problem solving style (RPS), avoidance style (AS), and impulsive/carelessness style.Materials and methods: The statistical population consisted of undergraduate students at Azad University- Rudehen branch in 2013. Participants (n= 387) were randomly selected via multistage method and completed general health questionnaire (GHQ-28), social problem solving scale-revised (SPSR) and self-efficacy scale (Sherer et al). For analyzing of data multiple regression test is applied.Results: The results showed that NPO and ICS can positively and self-efficacy can negatively predict total score of mental health difficulties. NPO and ICS have significantly positive relationship with somatic symptoms and anxiety. NPO and AS have significantly positive relationship with depression. Also NPO and AS have significantly positive relationship with social dysfunction, whereas RPS have significantly negative relationships with social dysfunction and self-efficacy negatively predicts depression.Conclusion: According to research findings, it is recommended that psychologists emphasize on teaching and improving social problem-solving skills and self-efficacy for preventing of mental health difficulties.